An Exploration of Approaches to the Support of Serendipity in Digital Environments - McCay-Peet, Lori; Quan-Haase, Anabel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
We explore how the common elements of serendipity identified in previous models may be used to identify different approaches to the design of digital environments to support serendipity. Three approaches are examined: social search, recommender systems, and visualization. Nous explorons la façon dont les éléments communs de la sérendipité identifiés dans des modèles précédents peuvent être utilisés pour identifier des approches différentes de la conception d'environnements numériques afin d’appuyer la sérendipité. Trois approches sont étudiées: la recherche sociale, les systèmes de recommandation, et la visualisation.